Recombinant plant gamma carbonic anhydrase homotrimers bind inorganic carbon - Martin, Victoria; Villarreal, Fernando; Miras, Isabelle; Navaza, Alda; Haouz, Ahmed; González-Lebrero, Rodolfo; Kaufman, Sergio; Zabaleta, Eduardo (FEBS Letters, 2009)
International audience Gamma carbonic anhydrases (cCA) are widespread in Prokaryotes. In Eukaryotes, homologous genes were found only in plant genomes. In Arabidopsis and maize, the corresponding gene products are subunits of mitochondrial Complex I. At present, only cCA homotrimers of Methanosarcina thermophila (CAM) show reversible carbon dioxide (CO 2) hydration activity. In the present work, it is shown that recombinant plant cCA2 could form homotrimers and bind H 14 CO À 3. However, they are unable to catalyse the reversible hydration of CO 2. These results suggest that plant cCAs do not act as carbonic anhydrases but with a related activity possibly contributing to recycle CO 2 in the context of photorespiration.